Steingo, Gavin. 2016. Kwaito’s Promise: Music and the Aesthetics of Freedom in South Africa. Chicago: University of Chicago Press - Clark, Emily Hansell (Current Musicology, 2018)
Gavin Steingo’s Kwaito’s Promise is an ethnographic monograph that “thinks with” kwaito, a black urban South African electronic popular music with roots in a short-lived period of euphoria surrounding the end of apartheid in the mid-1990s. As the hopefulness of that historical moment was quickly dispelled by the realities of a post-apartheid existence, kwaito persisted as feel-good dance music with lyrics that evoke context-free fun, such as “Let’s celebrate/It’s time to celebrate!” from the Trompies’ “Celebrate” (4). Critics of the genre have pointed to a dissonance between the aesthetic and lyrical tone of the music and the circumstances of its listeners’ and performers’ precarious lives in segregated and impoverished South African townships to characterize kwaito as “immature, apolitical, disconnected from social issues, and lacking any meaning or purpose” (vii). Steingo deconstructs these descriptors, unpacking longstanding assumptions about what it means for music to be political, to interact with social conditions, and to “have” meaning. Ultimately, he argues that kwaito’s musicians and audiences may well choose to ignore their social conditions through their engagements with the genre, but in doing so they “deliberately . . . invent another way of perceiving the world,” making kwaito “less a form of escapism than an aesthetic practice of multiplying sensory reality and thus generating new possibilities in the midst of neoliberalism’s foreclosure of the future” (vii–viii). In this review, I forego the standard format of chapter summaries and instead aim to situate Kwaito’s Promise more broadly in an intellectual lineage and a present scholarly moment that together point to possible, and, I argue, necessary directions for ethnomusicology’s own disciplinary future. In a sense, Kwaito’s Promise is a typical work of ethnomusicology, drawing from fieldwork in Soweto (a township of Steingo’s native city, Johannesburg) to attend ethnographically to a musical object, namely the practices and products that comprise the genre of kwaito, a genre historically tied to a specific population in a specific place. But Steingo does not merely describe and analyze kwaito as a musical genre or a product of social relations and history. Rather, he frames an encounter between a particular musical object and a particular body of theory (namely the political philosophy of Jacques Rancière) that produces reflections on both music and methodology and, ultimately, becomes a reflexive critique of knowledge production in the discipline with implications for humanistic scholarship more broadly. In doing so, Steingo joins a number of other ethnomusicologists since the 1980s who, rather than merely borrowing theory from other disciplines to apply to musical objects, bring humanistic theory and musical ethnography together in ways that contribute uniquely sonic perspectives to interdisciplinary conversations. Such scholarship does not just produce knowledge about music, but, moreover, results in scrutiny of the production of knowledge itself and the effects of scholarship in shaping and reinforcing already-held views of music, the social, and the human. In this review, I argue that such reflexively critical scholarship in ethnomusicology is not one current trend equal among many, but rather reflects a necessary sea change in humanistic scholarship. Kwaito’s Promise exemplifies the ways in which ethnomusicology cannot just follow the tides, but rather must actively contribute meaningful and unique perspectives to critical conversations across disciplines. Theoretically, Steingo draws primarily from the thought of Jacques Rancière on the politics of aesthetics and the “distribution of the sensible” (see also Moreno and Steingo 2012), both to understand kwaito and to reflect on how such scholarly understanding might be produced. Steingo argues that prior to its construction as a musical genre, kwaito is “an arrangement of sensory perception”—a sonic experience equal to any other in the sensory substance of its occurrence—that becomes a musical genre through production practices and social relations that are steeped in the economic and racial inequalities of post-apartheid South Africa. Through this interplay of equal sonic material and unequal social conditions, kwaito, Steingo claims, is able to “suspend normative modalities of hearing and knowing,” allowing its producers and listeners to double reality with another sonic reality that refuses to relinquish the hope for a future worth celebrating—a future that the end of apartheid once promised. The idea of an alternative reality and possible future that Steingo draws from Rancière resonates in the words of kwaito musicians and audiences, such as the “King of Kwaito” Arthur Mafokate, who describes the birth of present-day kwaito as a doubling of sonic material that already existed, with the possibility of alternative meaning: “We can’t call house music kwaito. Let’s create something out of what we call kwaito and call it kwaito” (56). Steingo’s analysis leads to an argument against a more meta form of inequality, namely ethnomusicology’s claims that no musician or listener can evade his or her “actual” social conditions, that purporting to do so is a form of ideological mystification, and that ethnomusicologists have access to the “truth” of what is “actually” going on behind the mystified words and actions of our interlocutors. Still thinking with Rancière, Steingo argues against the assumption of this privileged position for academics and academia, and instead argues that so-called “illusion” might be seen, instead of as a denial of “truth,” as a mode of generating a new sensory reality that is just as true, or, rather, that obviates truth as the goal of scholarship. Steingo argues that ethnomusicology of the last couple decades, largely concerned with demonstrating how music is a product of social relations and social conditions, has inadvertently become a generator of Rancière’s “knowledge which represses” by assigning “correct” ways of hearing and knowing to different groups and genres based on expertise. Kwaito’s Promise aims to exemplify another way. The Acoustic Assemblage A significant contribution of Kwaito’s Promise that exemplifies the book’s merits for audiences beyond Africanists and popular music scholars is Steingo’s furthering, in Chapter 5 (“Acoustic Assemblages and Forms of Life”), of the conceptual tool of the “acoustic assemblage,” previously formulated by Ana María Ochoa Gautier as “the mutually constitutive and transformative relation . . . generated between entities that hear, notions of the sonorous producing entities, and notions of the type of relationship between them” (Ochoa Gautier 2014, 23, emphasis in original). This formulation of a sonic act places emphasis on hearing as the starting point for a network of relations that involves not just a sound but rather a “notion” of what a “sonorous producing entity” might be, and a “notion” of a possible relationship between the source of a sound (the other) and the listener (the self). Acts, or even imaginaries, of sound thus always draw from and produce (or potentially challenge) the listening subject’s conceptions of the self, the other, and the relation between them in ways that “link sound to history, ecology, and cosmology” (Steingo 2016, 23) and are thus entangled with “the very definition of life” (Ochoa 2014, 5). Such a network of relations is generated around any subject who hears, and all entities can participate in multiple networks at the same time, producing a “radical openness” (Steingo 2016, 125) of relations that translates across domains of life and challenges the categories that are superimposed on lived experience (for example by the market or the state). Instead, within this openness is the potential to “hear the traces of a fundamentally different acoustic relation” (126) and thus an alternative understanding of the perceiving self, the perceptible other, and the relationship between them—in other words, of life itself. Steingo’s ethnographic material centers around musicians in Soweto who, in contrast to ethnomusicology and media studies’ frequent focus on the increasing mobility and circulation of music and musicians (e.g. Sterne 2012), are immobilized by various forms of precarity. Bound to the township by poverty and segregation, one of Steingo’s main interlocutors is further restricted to the space of his own home because leaving his music equipment (desktop computer, speakers, and bass guitar) unguarded almost guarantees its theft. Music made in Soweto is typically transmitted through the physical exchange of old hard drives, which are likely to corrupt files, fail completely, or disappear. Thus the “sonorous producing entities” of kwaito include not just musicians and instruments, but the heavily reused and repaired hard drive, the absence of stolen equipment, the failure of sound files to perfectly reproduce, and even the dogs used to guard homes from theft. Steingo uses the idea of the “acoustic assemblage” to situate kwaito, its producers, and its listeners in relationship with various “outsides”: temporal (the past and the future), spatial (places outside of the often very limited circulations of daily life), and cosmological (the domains of dreams and the occult, for example). The idea of the “spatial outside” provides an alternative to established ethnomusicological ways of thinking about place, such as “the local” and “the global.” Steingo argues that the implication of these terms that place operates in a scalar way—conceivable as concentric circles growing from the local to the national to the regional to the international with each level “larger” than and encompassing the former—does not make sense in attempts to understand his township- and home-bound Soweto friends’ experiences of space, mobility, and connection. Through the various acoustic assemblages that constitute kwaito, producers and listeners alike engage with other places, imagined and actual, bypassing notions of national or regional identity, and the immobilizing forces of segregation, poverty, and crime in the construction of an emplaced, cosmopolitan, intersubjective acoustic self. How to “Take Music Seriously” In the last decade, the overused phrase “taking [one’s object of study] seriously” has become a shorthand that argues opaquely for the scholar’s superior mode of thinking about the object in question compared to the existing literature, which has somehow failed to be sufficiently serious. But have all scholars of music not considered themselves to be “taking the question of music seriously”? Steingo uses the phrase to argue for a view of music not as a given category but “rather as a historically situated modality of experience” with “consequences [that] remain underdetermined but also, and precisely for this reason, compelling to think with” (xi). I take this to mean that for Steingo, “taking music seriously” must entail creating ethnomusicology as not just the discipline that studies the complex phenomenon of music, but rather as the grounds for interdisciplinary engagement around sonic objects and experiences, where contributions from aural perspectives can be made to the continued scrutiny of the production of knowledge about human practice and life. Through the interaction of political philosophical theory, ethnographic interviews, observations, and historicization around the object of kwaito, Kwaito’s Promise exemplifies an ethnomusicology that constructs itself as the grounds for humanistic theory at large to interact with and, moreover, to be acted upon by ethnographic explorations of sonic objects. I link Steingo’s work to that of other scholars who have succeeded in not just applying anthropological, philosophical, and other forms of humanistic theory to musical objects, but rather in exemplifying and arguing for ethnomusicology’s potential as a field where novel insights about humanity can be made. Marcia Herndon (1971), Steven Feld (1982), and Anthony Seeger (1987) proposed reconfigurations of Alan Merriam’s (1964) “anthropology of music” paradigm—i.e. the study of music in culture, entailing “the application of anthropological methods and concerns to music”—arguing instead for modes of examining music and sound as culture, as cultural systems that can reveal “an understanding of the ethos and quality of life in [a] society” (Feld 1982, 3), providing aural-oriented insight into the intertwining of ecology, cosmology, and aesthetics in the experience of life. In more recent years, while many ethnographic monographs have made worthy contributions to the accumulation of ethnomusicological knowledge, certain works have seen the meeting of humanistic theory and musical/acoustic ethnographic objects in ways that continue to argue for ethnomusicology’s potential as a crucible for transdisciplinary ideas that crystallize in unique ways around objects and instances of music and sound. For example, Amanda Weidman’s Singing the Classical, Voicing the Modern (2006), Ana María Ochoa Gautier’s Aurality (2014), and essays in Audible Empire edited by Ronald Radano and Tejumola Olaniyan (2016) interrogate the role of the aural in colonial knowledge production and point to sonic modes of postcolonial historiography. David Novak’s Japanoise (2013) brings an ethnographic study of noise to bear on media and circulation studies, rather than bringing media and circulation studies to bear on the concept of noise. Most recently, Licia Fiol-Matta’s The Great Woman Singer (2017) interrogates the role of voice in constructions of the human in twentieth-century Latin America from the perspective of gender and sexuality. (Notably, these scholars all work at the boundaries of ethnomusicology and sound studies, since questioning the production of musical knowledge almost necessarily entails the deconstruction of “music” as an object.) Steingo, likewise, creates space at the intersection of political philosophy and aural aesthetic forms, resulting in both an understanding of kwaito situated in contemporary South African politics and a critique of knowledge from the perspective of the listening subject as a creative entity, a generator of one’s own reality even from within the constricted lives of black South Africans after apartheid. Of course, using Rancière to understand kwaito is one possible route among many for theorizing what this particular genre does in the world and in the lives of its participants. But, I argue, what Kwaito’s Promise and the aforementioned works exemplify—taking music and ethnomusicology “seriously” as underdetermined grounds for the meeting of humanistic theory and aesthetic objects embedded in aural histories, with the potential to transform both interdisciplinary conversations as well as conceptions of the ethnomusicological project and of music itself—is not one possible route among many. Rather, Steingo and others who look critically at the way musical and aural knowledge have been produced—both in academia and in historical and present discourses of “common sense” (Radano and Olaniyan 2016)—are guiding the discipline on a necessary trajectory towards participation in the broader decolonization of knowledge. Tautological examinations of already-established concepts of music and culture might add to the canon of sufficiently described musical genres, but such studies fail to scrutinize the broader ways in which the musical and the aural (and ethnomusicology itself) have been complicit in the construction and perpetuation of ethnocentric and colonial forms of knowledge that have led to ongoing crises of governance, racial conflict, and climate change paralysis. For ethnomusicology to maintain relevance as a discipline, it must recognize its potential as a unique ground from which to interrogate the production of knowledge in broader conversations: to question the organization of sensory experience; to scrutinize concepts of music, creativity, and circulation in relation to profoundly unequal lives; to dismantle dichotomous understandings of “nature” and “culture” that the discipline has historically helped to construct as knowledge and as reality. The continued production of humanistic knowledge must also necessarily be a critique of the production of knowledge, and this can best be accomplished by understanding disciplinary distinctions not as modes of applying established or borrowed theory to various kinds of objects, but as participants in an interdisciplinary effort, in which different scholarly orientations can create space for new conversations, new intersections, new encounters, and new critiques. Kwaito and the Future of Ethnomusicology While Kwaito’s Promise exemplifies the above, it is not a perfect work. Steingo fails to fully extract himself from the cyclical paradox of the scholar deconstructing academia by proclaiming that his work is “different from the kind of mastery that trades on demystification and the search for truth behind illusion” (19). Producing a scholarly monograph that employs the language and ideas of philosophy from a white male tradition in order to look at black popular music is, it could be argued, its own form of mystification. Rancière is both critical of, and firmly situated in, a canon that does not offer its ideas up for easy, equal access—and Rancière himself is caught up in the conundrum of offering some of the best arguments for sourcing understandings of life from empirical experience rather than from reading Rancière. At times, the theoretical voices in Kwaito’s Promise drown out ethnographic informants’ own experiences and understandings, preventing these perspectives from speaking for themselves as Steingo (and Rancière) argue they should. While Kwaito’s Promise successfully exemplifies its own argument for music to be taken “as a historically situated modality of experience [that is] compelling to think with” in understanding diverse experiences of life, I see the potential for its theoretical engagements to expand more broadly. For example, “kwaito’s promise” refers to the promise of an alternative future through its celebratory aesthetic, a very different future from the one that South Africa’s current political and social conditions promise. Steingo uses Rancière to explore the idea of alternative futurities, with brief reference to Kofi Agawu’s call for a “future-oriented appraisal” of African music. But there is a vast literature on futurity left unexplored, not only by Africanists (such as Charles Piot’s Nostalgia for the Future) but also by feminist and queer scholars, who have been contending with the question of temporality at least since Julia Kristeva’s “Women’s Time” in 1981 (see McBean 2016 for a thorough review of this literature). While feminist and queer studies that deals with temporality has primarily taken literature and film as its objects of analysis, the temporal argument that Steingo constructs around kwaito could provide the empirical material for a conversation that brings together feminist/queer theory’s rich histories of questioning hegemonic temporalities and a sonic aesthetic object that brings in new voices and perspectives. Such a meeting of theory and object would exemplify a dismantling of the ghettos of academic thought. It would demonstrate, in other words, that feminist and queer theory are not relegated to discussing only objects that fall clearly under the purview of women’s and queer issues, but rather have much to offer to efforts to dismantle categories and hegemonic ways of thinking at large. Further, it would show that the ethnomusicological theoretical canon has no particular claims to having figured out the “correct” way to look at musical objects but could instead provide the grounds for interdisciplinary critical thought to encounter sonic objects and aural histories, with underdetermined results that could lead to important new insights. This is not to say that Kwaito’s Promise lacks a theoretical engagement that is necessary—indeed, every scholar must choose the literature that frames their theoretical engagement with an object from the limitless array, and Steingo’s concern and expertise lie in a canon of political philosophy that crystallizes in Rancière. I merely offer a suggestion for future possibilities that aims to take up Kwaito’s Promise’s promise: that music is “compelling to think with” beyond the established theoretical canon and apparatuses of ethnomusicology, instead offering a space for various disciplinary bodies of theory to interact around an aesthetic object or around the object of aesthetics itself, i.e. the various histories of how the sensible has been distributed. Kwaito’s Promise does vastly more than add kwaito to the list of genres that ethnomusicology has sufficiently described and analyzed. Steingo does not merely apply political philosophy to a musical object but allows musical ethnography to dialogue with philosophical ideas, offering an aural perspective on Rancière and hinting at ways that such meetings of humanistic theory and musical/sonic material might occur further. Steingo’s refusal to adopt standard ethnomusicological concepts of music, the social, and culture in his analysis of kwaito seems to heed Roy Wagner’s warning that when scholars in the Euro-American anthropological tradition create “culture” for Others through inherited, tautologically self-justifying modes of understanding human practice, “we make others part of a ‘reality’ that we alone invent, denying their creativity by usurping the right to create” (1975, 17). When we take the historical concept of “culture” as a given, we create culture and reality for individuals, precluding the possibility of those individuals creating their own understandings of self, life, and future. Steingo instead creates an underdetermined space of encounter between theory, ethnography, and musical object, where the words of interlocutors do not require demystification but rather speak to alternative ways of understanding musical creativity and the relations that comprise different experiences of life. I posit that Steingo and other ethnomusicologists who similarly critique the historical production of scholarly knowledge and exemplify new ways of allowing theory, ethnography, and sounding objects to interact are, following the sentiment of the “King of Kwaito” Arthur Mafokate, taking what we have called ethnomusicology, creating something new out of it, and calling it ethnomusicology. References Feld, Steven. 1982. Sound and Sentiment: Birds, Weeping, Poetics and Song in Kaluli Expression. Durham, NC: Duke University Press. Fiol-Matta, Licia. 2017. The Great Woman Singer: Gender and Voice in Puerto Rican Music. Durham, NC: Duke University Press. Herndon, Marcia. 1971. “The Cherokee Ballgame Cycle: An Ethnomusicologist’s View.” Ethnomusicology 15 (3): 339–52. McBean, Sam. 2016. Feminism’s Queer Temporalities. New York: Routledge. Moreno, Jairo and Gavin Steingo. 2012. “Rancière’s Equal Music.” Contemporary Music Review 31 (5–6): 487–505. Novak, David. 2013. Japanoise: Music at the Edge of Circulation. Durham, NC: Duke University Press. Ochoa Gautier, Ana Maria. 2014. Aurality: Listening and Knowledge in Nineteenth-Century Colombia. Durham, NC: Duke University Press. Piot, Charles. 2010. Nostalgia for the Future: West Africa after the Cold War. Chicago: University of Chicago Press. Radano, Ronald and Tejumola Olaniyan. 2016. Audible Empire: Music, Global Politics, Critique. Durham, NC: Duke University Press. Seeger, Anthony. 1987. Why Suyá Sing: A Musical Anthropology of an Amazonian People. Urbana: University of Illinois Press. Sterne, Jonathan. 2012. MP3: The Meaning of a Format. Durham, NC: Duke University Press. Wagner, Roy. 1975. The Invention of Culture. Englewood Cliffs, NJ: Prentice-Hall. Weidman, Amanda. 2006. Singing the Classical, Voicing the Modern: The Postcolonial Politics of Music in South India. Durham, NC: Duke University Press.